2004
DOI: 10.2105/ajph.94.3.452
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Registry Study of Infant Mortality in the Arctic: Greenland and Denmark, 1973–1997

Abstract: Postneonatal mortality rates in Greenland have decreased significantly during the past 25 years, but little progress has been made in decreasing neonatal mortality rates. Disparities exist among children with different maternal origins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…For boys with five-minute Apgar scores below 7, mortality before age 1 year was 28%, most of the deaths occurring among boys with scores below four. The overall mortality before age 1 year was 0.8%, which is consistent with the period nationwide estimates [ 35 ]. We had no information on potentially eligible men who may have been institutionalized for legal or health reasons.…”
Section: Discussionsupporting
confidence: 87%
“…For boys with five-minute Apgar scores below 7, mortality before age 1 year was 28%, most of the deaths occurring among boys with scores below four. The overall mortality before age 1 year was 0.8%, which is consistent with the period nationwide estimates [ 35 ]. We had no information on potentially eligible men who may have been institutionalized for legal or health reasons.…”
Section: Discussionsupporting
confidence: 87%
“…Despite a low birthweight rate, the infant mortality is high compared with Denmark (41), even when the same frequency of very low birthweight (below 1,500 grams) is seen. In general, the early mortality rate has been unevenly distributed within Greenland with more deaths in rural areas, many of which may have been preventable infant deaths (19,24). The deaths were spread over the whole birthweight distribution (24) as was also found among Alaska Natives (38), although data from 1987-1991 showed perinatal mortality to be especially frequent in children weighing 1,500 to 2,499 grams (19).…”
Section: Discussionmentioning
confidence: 99%
“…It resulted in identifying 7 publications. The abstracts were read and 3 articles, including research on birthweight, were analysed (24)(25)(26).…”
Section: Methodsmentioning
confidence: 99%
“…In a Danish population study of 678 consecutive live births of infants with OFC from 1977 to 1981, the mortality rate was 35 per 1000 (3.5%) (N = 24) before the age of 22 months 4 . The mortality rate of cleft infants in Denmark was higher compared to the general population’s post-neonatal mortality rate of 30 to 32 per 1000 (3.0 to 3.2%) reported in the same period 26 . A study of Dutch infants with isolated and non-isolated orofacial clefts reported the IMR to be elevated at 21 per 1000 (2.1%), which was significantly higher than the Dutch population IMR of 4.5 per 1000 (0.45%) 27 .…”
Section: Discussionmentioning
confidence: 61%